2016
DOI: 10.18632/oncotarget.13647
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels in control of pancreatic stellate cell migration

Abstract: Pancreatic stellate cells (PSCs) play a critical role in the progression of pancreatic ductal adenocarcinoma (PDAC). Once activated, PSCs support proliferation and metastasis of carcinoma cells. PSCs even co-metastasise with carcinoma cells. This requires the ability of PSCs to migrate. In recent years, it has been established that almost all “hallmarks of cancer” such as proliferation or migration/invasion also rely on the expression and function of ion channels. So far, there is only very limited information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…Since then it has been shown that PSCs possess Ca 2+ ‐activated K + channels (Storck et al . ) and it is therefore likely that initial Ca 2+ release from intracellular stores would activate such channels, promoting store‐operated Ca 2+ entry due to the more favourable electrochemical gradient provided by the hyperpolarized plasma membrane. Inhibition of excessive Ca 2+ signal generation in PACs and PSCs by partial blockade of CRAC channels is a promising therapeutic avenue in many inflammatory diseases (Parekh, ; Di Capite et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since then it has been shown that PSCs possess Ca 2+ ‐activated K + channels (Storck et al . ) and it is therefore likely that initial Ca 2+ release from intracellular stores would activate such channels, promoting store‐operated Ca 2+ entry due to the more favourable electrochemical gradient provided by the hyperpolarized plasma membrane. Inhibition of excessive Ca 2+ signal generation in PACs and PSCs by partial blockade of CRAC channels is a promising therapeutic avenue in many inflammatory diseases (Parekh, ; Di Capite et al .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CRAC channel inhibition markedly reduces the prolonged [Ca 2+ ] i elevation due to the store-operated Ca 2+ entry into the PSCs that follows the initial BK-elicited intracellular Ca 2+ release ). Since then it has been shown that PSCs possess Ca 2+ -activated K + channels (Storck et al 2017) and it is therefore likely that initial Ca 2+ release from intracellular stores would activate such channels, promoting store-operated Ca 2+ entry due to the more favourable electrochemical gradient provided by the hyperpolarized plasma membrane. Inhibition of excessive Ca 2+ signal generation in PACs and PSCs by partial blockade of CRAC channels is a promising therapeutic avenue in many inflammatory diseases (Parekh, 2010;Di Capite et al 2011) including AP (Gerasimenko et al 2013(Gerasimenko et al , 2014Wen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, MSCs migrated into the tumor negatively modulate anti-cancer immunity via their interaction with immune cells [87][88][89] . Ion transporters and channels in the plasma membrane participate in the regulation of cell motility [90][91][92][93][94] . There is also evidence for the contribution of hHv1 to cell migration, e.g.…”
Section: Discussionmentioning
confidence: 99%